Intercultural Learning: A Promising Pedagogy in the New Millennium - Echcharfy, Mouhssine (Yayasan Visi Intan Permata, 2019)
In a multicultural context, most of the common problem among individuals is that people hold an ethnocentric perspective, as they tend to idealize their own culture and ignore cultural difference. In this regard, interculturalism has come into play as it encourages ethno-relative perspective in that it stresses the importance of openness to and acceptance of different beliefs, values and customs (e.g., Coulby, 2006; Lentin & Titley, 2011; O?Cinneide, 2012; Jokikokko & Karikoski, 2016).This intercultural trend has led to the emergence of a new language pedagogy called ?Intercultural Learning? that aims at promoting intercultural competence in EFL classrooms and prepare EFL learners to meet the challenges of such a globalized world. The thrust of the argument in this paper is that culture courses should not be a place where learners are exposed only to the target culture; it should rather be a place where learners can experience cross-cultural situations, reflect on their experience, and act as intercultural speakers/mediators with the ability to communicate and interact appropriately and effectively in different intercultural situations. It offers insights into the challenges that lead to the emergence of intercultural learning. It also gives an account of the importance of culture in language learning. The paper discusses intercultural learning pedagogy, as it defines the notion of intercultural learning, discusses its principles and explains the key element of intercultural learning ?experiential learning? and how it is implemented. It also provides implications for teachers at the university level.